Cytat w działaniu. Studium przypadku tekstoterapii kulturowej na podstawie wystawy Izba przyjęć rzeczy biednych. Re_KOLEKCJE z Kantora - Kapusta, Anna (2017)
The article was dedicated to the authorial concept of cultural textual therapy, which was implemented by me as a part of a temporary exhibition entitled Admissions Ward for Poor Objects. Re_COLLECTIONS from Kantor Exhibition. The exhibition took place at the Ethnographic Museum in Kraków from 30th October to 20th December 2015. The exhibition was curated by Olaf Cirut, Anna Kapusta and Katarzyna Piszczkiewicz. Cultural textual therapy is a process supporting personal development through the a moderated act of reading, which may be participating in an exhibition. The exhibition entitled Admissions Ward for Poor Objects. Re_COLLECTIONS from Kantor intensified the relationship between the spectator (equivalently: the creator and the recipient) and the collectible. The method of working with a collectible, which was derived from the artistic practice of Tadeusz Kantor was used. An important role was played – in the symbolic space of this exhibition – by verbal cultural texts, which were quotes from the writings of Kantor. The quotes become (in addition to the collectibles) equivalent objects, which were made available to participants of the exhibition. The strategy of cultural textual therapy was based on (in metaphorical way) intensive interactions between objects of exhibitions and individual styles of their reception. The case study of this project is also devoted to ethnography of quotation at the exhibition. According to this ethnography a quote becomes each of us – individual participant of the exhibition. The quote, interpreted as an independent text of culture, moderates and implements conscious participation. In this way, the museum and the gesture of exhibition represent an institutional framework for cultural textual therapy.
Keywords: personal development; quotation; temporary exhibition; cultural textual therapy; The Ethnographic Museum in Kraków